2022
DOI: 10.1155/2022/7379334
|View full text |Cite
|
Sign up to set email alerts
|

How Does COVID-19 Affect Traffic on Highway Network: Evidence from Yunnan Province, China

Abstract: The COVID-19 pandemic and antipandemic policies have significantly impacted highway transportation. Many studies have been conducted to quantify these impacts. However, quantitative analysis of the impacts on province-wide traffic in developing countries, such as China, is still inadequate. This paper tried to fill this gap by proposing equations to quantify the traffic variations of overall province-wide traffic and to analyze the intercity bus traffic variation and intercity bus usage, applying the K-means c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The discussion of challenges posed by COVID-19 in transport mostly focuses on negative impacts and their mitigation. However, it is worth mentioning some unintended positive effects linked with transportation: reduction of pollution and waste (Erkhembayar et al, 2020;Haque et al, 2021), significant decline in traffic (Li et al, 2022), positive impact on road freight transport turnover (Ho et al, 2021), rapid progress in digitisation and implementation of innovations in the transport sector (Subramanya & Kermanshachi, 2021), and robotisation (Zeng et al, 2020). As a result of COVID-19's multifaced and severe implications, risk management in the supply chain has become an intensively explored area of scientific research.…”
Section: Literature Review On Transportation Risksmentioning
confidence: 99%
“…The discussion of challenges posed by COVID-19 in transport mostly focuses on negative impacts and their mitigation. However, it is worth mentioning some unintended positive effects linked with transportation: reduction of pollution and waste (Erkhembayar et al, 2020;Haque et al, 2021), significant decline in traffic (Li et al, 2022), positive impact on road freight transport turnover (Ho et al, 2021), rapid progress in digitisation and implementation of innovations in the transport sector (Subramanya & Kermanshachi, 2021), and robotisation (Zeng et al, 2020). As a result of COVID-19's multifaced and severe implications, risk management in the supply chain has become an intensively explored area of scientific research.…”
Section: Literature Review On Transportation Risksmentioning
confidence: 99%
“…The results showed a non-linear relationship between intercity travel and pandemic mainly due to the change of control policy. The travel pattern analysis on highway network was conducted based on the trajectory information (Li et al, 2022), and the tra c ow pattern was de ned as before pandemic, during pandemic and recovery stage. On the other hand, a few of researches focused on the urban transportation system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twenty-four studies report the impact of the COVID pandemic on the demand for different freight transport modes, i.e., air, maritime, rail, and road. Six studies examine the impact of COVID-19 on the demand for seaports and waterways transport [6,7,9,37,[39][40][41][42][43]. Tianming, Erokhin, Arskiy and Khudzhatov [9] show that the pandemic breaks the connectivity among seaports in China, Norway, Iceland, Russia, South Korea, and Sweden.…”
Section: Source Citation Analysismentioning
confidence: 99%
“…Gray [32] reports an increasing demand in the agriculture sector for different transportation services, e.g., bulk ocean freight, rail movement, and road trucks. Li, Bai, Hu, Yu and Yan [42] present equations to evaluate the traffic variations of overall provincewide traffic and tested the hypotheses for traffic recovery analysis. The results show that truck traffic dropped by 68.19% during the outbreak and found that the higher the GDP per capita the region has, the more the traffic in the region was affected by the pandemic.…”
Section: Source Citation Analysismentioning
confidence: 99%